Steel Corrosion Control in Seawater Using Zinc sacrificial anode - Mohamed A. Khalil , Elfitouri K. Ahmied (Journal of Pure & Applied Sciences, 2019)
The samples surface preparation has been conducted using electrical machining, well electrical wires have been connected to the upper ends of both test samples, for electrochemical potential measurements. Both samples have been fully immersed in natural seawater environment. Test was conducted according to ASTM G31 immersion corrosion testing. Visual examination (VE), optical photograph on each test sample have been conducted The obtained results have been compared and found to be well correlated. It was found that un cathodically protected test sample has been completely covered by corrosion product, whilst the cathodically protected steel test sample found to be covered with a dense and homogeneous calcareous deposit film and free from any sign of corrosion as expected. According to the obtained results from all used monitoring methods it can be concluded that full cathodic protection has been achieved to the cathodically protected steel test sample in aerated natural seawater, whilst un cathodically protected steel test sample has been severely corroded in the a/m environment and the corrosion rate by means of weight loss coupon method found to be 3 mpy which reduced to only 0.25 mpy this means that the achieved protection efficiency % after application of Cathodic Protection was 91%. The required protection current density of bare mild steel in static natural seawater could be reduced to 82% folds, if a well film of calcareous deposit been maintained.